Reflection of torsional T(0,1) guided waves from defects in pipe bends - Heinlein,S; Cawley,P; Vogt,TK (NDT and E International, 2017)
This paper investigates the reflection of the torsional T(0,1) mode from defects in pipe bends. The effect of varying circumferential and angular position along the pipe bend, as well as the influence of the bend radius, is investigated via 3D finite element simulations. The results show that the reflection expected from a small defect varies significantly with position, the minimum reflection coefficient being about 10% of that from a comparable defect in a straight pipe, while maxima of around four times the straight pipe value are seen. The areas of low detectability are mainly found on the bend intrados and those of high detectability close to its extrados; similar effects are seen in bends with radii varying from one to twenty pipe diameters. It is shown that the reflection from a defect at a given location is roughly proportional to the square of the von Mises stress produced by the transmitted wave at that position. This holds for defects such as circumferential cracks, the detailed subject of this investigation, and is also expected to be valid for corrosion patches; it will not hold for axial cracks. The results explain the low reflection seen from a simulated corrosion defect at a bend in a previous investigation.